Will higher wages benefit the economy? the effects of labor income share on macroeconomic variables in Malaysia - Ngaini, Nurul Sakinah; Saari, Mohd Yusof; Abd Rahman, Muhammad Daaniyall; Habibullah, Muzafar Shah; Hashim, Muhamad Zharif Luqman (Universiti Malaysia Sabah Press, 2024)
In Malaysia, household expenditure drives about 60% of the economy. This suggests that increasing aggregate demand is crucial for economic growth. As demand is a function of labor income, raising the latter puts more money into the pockets of consumers, which eventually facilitates feedback effects on the goods and factor markets and potentially triggers macroeconomic structural changes. Having these effects in hand raises a concern on the extent to which the increase in labor income could influence selected macroeconomic variables, such as shadow economy, female labor force participation rate, technology, labor productivity, foreign workers, and skilled-related underemployment. These are some structural issues pointed out in the Twelfth Malaysia Plan (2021-2025). In the pursuit of achieving targets to increase labor income to GDP from 37.1% in 2020 to 40% by 2025, this paper attempts to examine the impact of labor income on the selected macroeconomic variables using annual data from 2005 to 2021 and employing the Ordinary Least Square (OLS) with robust standard error due to Newey-West procedure. Our results indicate that the labor income could boost female labor force participation rate, labor productivity, and technological innovation. Meanwhile, it is also found that increase in the labor income could dampen the prevalence of shadow economy, skilled-related underemployment, and dependency on foreign workers at various skill levels. Therefore, a policy that targets improving labor income could have greater potential to solve various structural issues inflicted on the nation for decades. Whilst the present study provides empirical evidence on the macroeconomic perspective, it is of great importance for the policy makers to gauge a deeper understanding on such effects at the microeconomic side.